GAYA KOMUNIKASI YOUTUBER MEDY RENALDY DALAM MEREVIEW ACTION FIGURE DI YOUTUBE - Avaldo Jales Nugroho; Wirda Yulita Putri (Bajang Institute, 2024)
Communication style is a person's way of interacting with others with the intention of providing an understanding of the verbal and nonverbal messages conveyed by the communicator as the sender of the message to the communicant as the recipient of the message depending on the situation at hand. This study aims to describe the communication style used by Medy Renaldy in the action figure review video content on Medy Renaldy's youtube channel by using data obtained from in-depth interviews with informants and observations on the 3 most watched action figure review videos on Medy's youtube channel. Renaldy. This research is a qualitative research with case study method. The results of the study found that the communication style used by Medy Renaldy in the action figure review video content on Medy Renaldy's youtube channel was the equalitarian style, as well as the discovery of aspects contained in Medy Renaldy's communication style, namely dramatic and friendly, and the use of verbal and nonverbal communication. that Medy Renaldy uses, such as gestures, facial expressions, and intonation, as well as obstacles that come to Medy Renaldy.